2017
DOI: 10.1158/1538-7445.sabcs16-s1-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S1-01: Whole exome and transcriptome sequencing of resistant ER+ metastatic breast cancer

Abstract: Background: While great strides have been made in the treatment of estrogen receptor-positive (ER+) metastatic breast cancer (MBC), therapeutic resistance invariably occurs. A better understanding of the underlying resistance mechanisms is critical to enable durable control of this disease. Methods: We performed whole exome sequencing (WES) and transcriptome sequencing (RNA-seq) on metastatic tumor biopsies from 88 patients with ER+ MBC who had developed resistance to one or more ER-directed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…We found numerous genetic variants present in both fulvestrant- and tamoxifen-resistant cells, and GSEA showed that the expression of genes downstream of some of the genetic variants were significantly altered (Figure 6I and Table S6). Several of the genetic variants found in both FULVR and TAMR cells were related to glutamate metabolism (e.g., HIF1A , PCDHGA12 , TMX4 , and TNR ) and almost all of them were also detected in metastatic lesions of breast cancer patients resistant to endocrine therapies (Cohen et al, 2017) confirming their physiologic relevance.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…We found numerous genetic variants present in both fulvestrant- and tamoxifen-resistant cells, and GSEA showed that the expression of genes downstream of some of the genetic variants were significantly altered (Figure 6I and Table S6). Several of the genetic variants found in both FULVR and TAMR cells were related to glutamate metabolism (e.g., HIF1A , PCDHGA12 , TMX4 , and TNR ) and almost all of them were also detected in metastatic lesions of breast cancer patients resistant to endocrine therapies (Cohen et al, 2017) confirming their physiologic relevance.…”
Section: Resultsmentioning
confidence: 88%
“…Normalized microarray gene expression and clinical data of a cohort of 132 primary tumors from tamoxifen-treated patients followed up more than 5-years were obtained from GEO accession number GSE9893 (Chanrion et al, 2008). We also analyzed an unpublished dataset of RNA-seq gene expression RPKM (Reads Per Kilobase of transcript, per Million mapped reads) of a cohort of 109 ER + distant metastases that are part of the Metastatic Breast Cancer Project (Cohen et al, 2017). Breast cancer patients were >18 years of age and all but one female.…”
Section: Star*methodsmentioning
confidence: 99%
“…For the subsequent hypermutated cohort analysis, we also included 8 additional patients (from a cohort of 222 patients) from our ongoing study of estrogen receptor (ER)-positive metastatic breast cancer in the Center for Cancer Precision Medicine at Dana-Farber Cancer Institute (DFCI-CCPM). 24 Prior to any study procedures, all patients provided written informed consent to whole exome sequencing of tumor and normal DNA, as approved by the Dana-Farber/Harvard Cancer Center Institutional Review Board (DF/HCC Protocol 05-246). Metastatic core biopsies were obtained from patients and samples were immediately snap frozen in optimal cutting temperature and stored in -80°C.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…We hypothesized that hypermutated breast cancers may respond to immune checkpoint inhibitors regardless of the underlying mutational signature. To test this, we examined the treatment histories of 222 patients with metastatic breast cancer from our prospective metastatic biopsy cohort at DFCI 24 . We identified 8 pts (3.6%) with hypermutated breast cancer, of whom four had received treatment with anti-PD-1/PD-L1 based therapies.…”
Section: Response To Anti-pd-1/pd-l1 Based Therapies In Hypermutated mentioning
confidence: 99%
“…The breast cancer model and its predictions will serve as a basis for guiding and interpreting drug resistance and drug combination studies in the context of ER+ and/or HER2+ breast cancer. The model can be expanded to incorporate multiple genetic alterations observed in breast cancer patient cohorts (38,40,76,77) by introducing these alterations into the model appropriately (e.g., as a node activation or inactivation). The inclusion of the most probable intrinsic or acquired resistance mechanisms to a treatment, informed by pre-, on-and post-treatment genetic characterization of tumors (77), will allow the identification and ranking of the combinatorial interventions that are effective even in the presence of tumor drug resistance.…”
Section: Discussionmentioning
confidence: 99%